Analisis Penggunaan bahasa promosi Influencer Tiktok dalam Iklan Glad2glow terhadap Minat Beli Gen Z : Penelitian - Afriyani Elizabet Sitorus; Aqilah Apritia Parawanza; Helena Seprina Sitohang; Rachel Adeline Siagian; Trisnawaty Hutagalung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the use of promotional language by influencers on TikTok in Glad2Glow skincare advertisements and its influence on Generation Z’s purchase intention. The research is motivated by the increasing role of influencer marketing in social media, particularly TikTok, which has become a dominant platform among Gen Z. This study employed a descriptive qualitative approach with data collected through semi-structured interviews with 15 respondents aged 18–25 years in Medan who actively use TikTok. The results show that most respondents were exposed to Glad2Glow advertisements and admitted that casual, authentic, and relatable promotional language successfully captured their attention and sparked curiosity. However, only a small portion of respondents expressed an actual purchase intention. Trust was identified as the most dominant factor bridging interest and purchase decisions, while advertisement visualization only played a supporting role. These findings indicate that the effectiveness of promotion is not solely determined by language style but also by the integration of persuasive communication, creative visuals, and influencer credibility. This research contributes theoretically to the study of digital marketing communication from the perspective of promotional linguistics and provides practical recommendations for local brands to strengthen